Unravelling the Origins of Kurdish Literary Heritage: Challenges and Perspectives - Ali, Aram; Abdalla, Shabaz (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
The present paper aims at exploring the complex processes of emergence of Kurdish literary culture with an emphasis on the history of Kurdish written poetry and the cultural context that has contributed to its development. Such works as the poems of Baba Tahir provide the primary basis for the research that alters the understanding of plagiarism and authenticity of Kurdish literature. By dint of close reading of key texts and historical periods, the research thus highlights the importance of critical appreciation in assessing literature. It reflects on the timeless enigmatic nature of Kurdish literature that further stresses the importance of the comprehension of its roots and values. This study offers a clearer understanding of the complexity of the Multiple Layers of Ambiguity in the context of Kurdish poetry and serves as a reminder of the significance of further historical and comparative analysis of Kurdish and other related poetic traditions. The study also underlines the need for cooperation between scholars working in academia in order to find a solution to the problem and to capture the essence of the Kurdish literature origins.